2020
DOI: 10.1016/j.polgeo.2020.102219
|View full text |Cite
|
Sign up to set email alerts
|

Fighting over friends and neighbors: The effect of inter-candidate geographic distance on intra-party competition

Abstract: Previous studies on intra-party competition have largely neglected the role played by geographic distance between co-partisan candidates. In this paper, we argue that candidates who live further away from intra-party competitors on the same party list benefit electorally from their remoteness. Moreover, we contend that the electoral effectiveness of exhibiting local personal vote attributesa theoretically and empirically well-established candidate strategy to cultivate personal votesalso depends on the geograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…With the Kainuu incumbent Ulla Parviainen fighting for her parliamentary life in 2019 -she gained 87.7% of her personal vote in her home municipality of Kuusamo 4 years earlier -she managed only 8% of her total personal vote from neighbouring Taivalkoski where there was no local KESK candidate (cf. Put et al 2020). She was not re-elected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the Kainuu incumbent Ulla Parviainen fighting for her parliamentary life in 2019 -she gained 87.7% of her personal vote in her home municipality of Kuusamo 4 years earlier -she managed only 8% of her total personal vote from neighbouring Taivalkoski where there was no local KESK candidate (cf. Put et al 2020). She was not re-elected.…”
Section: Resultsmentioning
confidence: 99%
“…The electoral value of localness -the home turf advantage -may be diminished by the presence of proximate co-partisan rivals with competing claims to localness. Moreover, the vote increment accruing from localness, based on a candidate's exclusive and/or hegemonic position in the primary electoral constituency à la H1 -or what Put et al (2020) refer to as candidate 'localness and remoteness' -may be undermined by the pull of a highprofile outsider who will skew the distribution of the candidate vote across the district. Put another way, localness and remoteness will be trumped by the appeal of a nationally known 'offcomer' who may not even need to canvass to attract votes in the locality.…”
Section: Hypothesising On Patterns Of Intraparty Competitionmentioning
confidence: 99%
“…However, another stream of European research on "personal votes" in parliamentary regimes showed that the effect of birthplace is magnified under "open-list" electoral systems where more intraparty competition occurs (Shugart, Valdini, and Suominen, 2005). Localness as a "shortcut" to guide voter choice under open-list representation was also reported in Hamburg, Germany (Jankowski, 2016), Estonia (Tavits, 2010), Belgium (Put and Maddens, 2015), and Finland (Put, Schoultz, and Isotalo, 2020). Because general elections provide the strongest alternative voting "cue" to using localism, namely the candidates' party affiliations, Hypothesis 1 posits that F&N effects will be stronger in primary elections than in general elections.…”
Section: Friends and Neighbors Here And Abroadmentioning
confidence: 99%
“…Therefore, we control for a number of municipal-level covariates that could, on average, impact voters' evaluation of the candidates' choice set. We control for the number of inhabitants, the geographical size of a municipality (Lewis-Beck & Rice, 1983), its degree of urbanization (Blais et al, 2003;Meredith, 2013), and whether another local candidate is running for office (Put, von Schoultz, & Isotalo, 2020).…”
Section: Data Measures and Identification Strategymentioning
confidence: 99%